The kafala institution in Spain and the constitution of International Child Adoption. Article 19.4 Of the Spanish act 54/2007 - Herranz Ballesteros, Mónica (CUADERNOS DE DERECHO TRANSNACIONAL, 2021)
International adoption in Spain of a marroquian child after a Kaflah in her country of origin. Spanish citizens with habitual residence in Spain. The application of article 19.4 of the International Adoption Law in such cases.